Patellar Instability Factors in Isolated Medial Patellofemoral Ligament Reconstructions—What Does the Literature Tell Us?: A Systematic Review. (September 2015) - Tompkins, Marc A.; Arendt, Elizabeth A.
Background: Many studies have demonstrated good results after medial patellofemoral ligament (MPFL) reconstruction for patients with patellar instability. The applicability of published studies to the clinical decision-making process for the individual patient with patellar instability, however, is not well elucidated. Hypothesis: There is inconsistency in the reporting of preoperative and postoperative variables, which limits the applicability of current studies to patients with patellar instability. Study Design: Systematic review. Methods: A systematic review of the literature was conducted using the search term medial patellofemoral ligament reconstruction to identify studies with cohorts of patients with isolated MPFL reconstruction. A combination of inclusion and exclusion criteria resulted in 24 studies being reviewed for a variety of preoperative demographics, physical examination findings, and imaging findings, as well as postoperative outcomes, including redislocation and responses to subjective questionnaires. Results: A physical examination of lateral patellar translation was reported in 42% of studies, by reporting an apprehension sign (n = 9), reporting quadrant translation (n = 7), or both. For patellar instability factors on imaging, patellar height was reported as a preoperative variable in 75% of studies, and trochlear dysplasia was reported in 83% of studies. The tibial tubercle–trochlear groove distance was reported as a preoperative variable in 42% of studies. The rate of redislocation after index surgery was reported in 92% of studies. Patient-related outcome measures were reported in all of the studies; the Kujala score was the most common. A homogeneous population was selected as part of the authors' surgical indications for "isolated" MPFL in 67% of studies, and a heterogeneous population was selected in 33% of studies. Conclusion: Current literature on MPFL reconstruction contains diverse methods of recording preoperative and postoperative variables. Most studies report on a homogeneous population, with inconsistent applicability to the broad spectrum of patients with patellar instability. Outcomes reporting in our current literature needs more clarity and consistency regarding reporting methodology to be of value for the treating clinician.